Recombinant human growth hormone treatment in infants with chronic renal failure. Issue 1 (January 1996) - Maxwell, H; Rees, L
Abstract : Poor growth is a particular problem for children with congenital renal disease. A one year trial of the use of recombinant human growth hormone (rhGH) in eight infants and young children with chronic renal failure is reported here. At entry bone age was less than 2 years, mean (range) chronological age 1.9 (1.3-2.7) years, and glomerular filtration rate (GFR) was 17 (9-42) ml/min/1.73 m2. Height standard deviation score (SDS) was -3.3 (-4.6 to -2.0) and height velocity SDS was -1.3 (-3.1 to 0.7). One child was withdrawn when he received a renal transplant after 9.5 months. Two children required dialysis, but remained in the trial. Treatment with rhGH resulted in an increase in height SDS to -2.2 (-4.2 to -0.9), p = 0.0002, and height velocity SDS to 1.1 (-0.7 to 2.6), p = 0.006. There was no change in GFR and no serious adverse events. There was no effect on plasma lipids, calcium, phosphate, intact parathyroid hormone, or glucose. Alkaline phosphatase rose significantly. Thus rhGH improved growth in eight infants with chronic renal failure, with four children entering the normal range.